Suriname : Technical Assistance Report. (IMF Staff Country Reports; Country Report, 2018)
This Technical Assistance Report on Suriname constitutes technical advice provided by the staff of the IMF to the authorities of Suriname in response to their request for technical assistance. The mission discussed issues concerning the consumer price index (CPI), the producer price index (PPI) and export price index (XPI). On the CPI, the mission reviewed current practices and provided some recommendations. The main recommendations are to switch from a Dutot to a Jevons index on the elementary aggregate level and to start publishing the CPI according to the Classification of Individual Consumption according to Purpose on a class level provided the number of items permits. On the planned PPI and XPI, the discussion focused on available data sources and next steps for developing a PPI for Suriname. Reliable price statistics are essential for informed economic policymaking by the authorities. They also provide the private sector, foreign investors, rating agencies, and the public in general with important inputs in their decision-making, while informing both domestic economic policy and IMF surveillance.